Men and women waiting for mail at the post office, Dawson, Yukon Territory, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Waiting for mail at Dawson City Post Office" Shows advertisement for A.J. Bannerman and Company, Mine Brokers.